Formation of advanced glycation end‐products in glycation of silver carp myofibrillar protein with glucose: Relationship with its chemical indicators. (2nd November 2022) - Ren, Yanmei; Mao, Zhenjie; Zhang, Qi; Dong, Shiyuan; Zha, Fengchao; Chen, Bojian
Summary: The formation of advanced glycation end products (AGEs), regarded as a potentially harmful substance, in the protein glycation course is still under investigation. This study investigated the glycation modification of silver carp myofibrillar protein (MF) with glucose via Maillard‐driven chemistry. The resultant conjugates and glycation extent were characterised by chemical indicators, such as Fourier transform infrared spectroscopy, sodium dodecyl sulphate–polyacrylamide gel electrophoresis, colour development, and AGEs level. As the primary responsibility for glycation, the loss of Lysine (Lys) and Arginine (Arg) in MF with longer glycation time (>24 h) was more than 25%. While, the associated AGEs, including Nε‐carboxymethyl‐lysine (CML), Nε‐carboxyethyl‐lysine (CEL), and methylglyoxal‐derived hydroimidazolone 1 (MG‐H1), presented a gradually increasing tendency with glycation time. The kinetic studies indicated that the formation of CML and MG‐H1 presented a highly linear correlation with heating time, while the CEL development could be described as an exponential function of glycation time ( r  ≥ 0.95). Moreover, the correlation analysis among these chemical indicators indicated that colour development was positively correlated with AGEs ( r  ≥ 0.85), while negatively related to the loss of Lys and Arg ( r  ≤ −0.89). The findings may help to better control the glycation course of food protein based on the formation of AGEs. Abstract : This is the paper to systematically investigate the chemical characterisation and the formation of AGEs in the glycoconjugates from silver carp myofibrillar protein and glucose with heating time. The findings may help to better control the glycation process of fish protein based on the loss of essential amino acid and AGE level.